Radiographic Measurements Associated with Ankle Power Generation During Gait in Patients with Cerebral Palsy - Yoon Hyo Choi MD; Dong Yeon Lee MD, PhD; Min Gyu Kyung MD, PhD; Kyoung Min Lee; Kyoung Min Lee (Foot & Ankle Orthopaedics, 2023)
Category: Basic Sciences/Biologics; Ankle Introduction/Purpose: Pes planovalgus (PV) deformity accounts for lever arm dysfunction and compromises gait in patients with cerebral palsy (CP). However, the association between ankle power generation and radiographic indices is not yet understood. We aimed to investigate the association between ankle power and radiographic indices during gait in patients with CP concomitant with PV deformity. Methods: Patients older than 14 years with ambulatory CP and PV deformity were included. All the patients underwent three- dimensional gait analysis and weight-bearing foot radiography. Gait data were collected, including foot progression angle, tibial rotation, and ankle power generation. Radiographic measurements included anteroposterior (AP) talo-first metatarsal angle, lateral talo-first metatarsal angle, and hindfoot angle. A linear mixed-effects model was used for statistical analysis to identify significant radiographic indices associated with ankle power generation. Results: Thirty-one limbs from 15 patients with spastic diplegia and six with spastic hemiplegia were included. Statistical analysis demonstrated that ankle power generation was significantly correlated with the CP type (p=0.01) and AP talo-1st metatarsal angle (p=0.02). Conclusion: Ankle power generation was significantly associated with the AP talo-first metatarsal angle. Surgeons might need to pay attention to correcting forefoot abduction to restore ankle power when planning surgeries for pes PV deformities in patients with CP.